PELATIHAN PENGOLAHAN BUNGA TELANG MENJADI MINUMAN KHAS MEKAR MULIO MELALUI BRANDING PRODUK DAN DIGITAL MARKETING - Aris Siregar; Herman Herman; Jihan Aprilia; Novita Sari; Hilmiatus Sahla (Smart Education, 2025)
Abstract: Training and mentoring in processing butterfly pea flowers into a specialty drink in Mekar Mulio Village, Asahan Regency, was conducted as a form of community empowerment based on local potential. This activity aimed to improve the community's skills in processing butterfly pea flowers into a beverage with economic value and to introduce branding and digital marketing strategies as promotional tools. The implementation method consisted of socialization, hands-on training, product development mentoring, and training in the use of digital media for marketing. The results showed that the community was able to produce high-quality butterfly pea flower drinks, with attractive packaging, and a strong brand identity, namely